The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1074/jbc.m007640200
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum (ER)-associated Degradation of T Cell Receptor Subunits

Abstract: Degradation of proteins from the endoplasmic reticulum is fundamental to quality control within the secretory pathway, serves as a way of regulating levels of crucial proteins, and is utilized by viruses to enhance pathogenesis. In yeast two ubiquitin-conjugating enzymes (E2s), UBC6p and UBC7p are implicated in this process. We now report the characterization of murine homologs of these E2s. MmUBC6 is an integral membrane protein that is anchored via its hydrophobic Cterminal tail to the endoplasmic reticulum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 36 publications
(46 reference statements)
2
96
1
Order By: Relevance
“…Retention in the ER and subsequent breakdown of αTCR in the absence of other TCR subunits is one of the best studied examples of ERAD [5][6][7]12,20,[38][39][40][41][42][43][44][45]. ERAD is generally regarded as a UPS-dependent process requiring VCP Ufd1-Npl4 for retrotranslocation of substrates from the ER into the cytosol [19,25,26,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retention in the ER and subsequent breakdown of αTCR in the absence of other TCR subunits is one of the best studied examples of ERAD [5][6][7]12,20,[38][39][40][41][42][43][44][45]. ERAD is generally regarded as a UPS-dependent process requiring VCP Ufd1-Npl4 for retrotranslocation of substrates from the ER into the cytosol [19,25,26,46].…”
Section: Discussionmentioning
confidence: 99%
“…It is not known what specific structural feature or association with what protein triggers αTCR ubiquitination, but it is required not only for its targeting to the 26S proteasomes, but also for its retrotranslocation from the ER [11,12]. Ubiquitination of αTCR is mediated by at least two different ubiquitin ligases (E3s): cytosolic SCF Fbs1,2 which recognizes N-linked oligosaccharides attached to dislocated αTCR chain [13] and ER-membrane associated HRD1 [14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a truncated form with the putative SP and the PA domain removed was evenly distributed in the whole cell ( Figure 1E2). More convincingly, GFP-Rnf133 co-localized with the RFP-tagged E2 conjugating enzyme MmUbc6, an endoplasmic reticulum (ER)-localized protein [7] ( Figure 1F). These data indicated that Rnf133 was most likely an ER-associated protein.…”
Section: Dear Editormentioning
confidence: 91%
“…ERAD constitutively counteracts ER stress, eliminating misfolded proteins from the ER, but it is further activated as part of UPR (Casagrande et al, 2000;Friedlander et al, 2000). Expression of individual TCR subunits in cell lines which endogenously do not express TCR have served in numerous studies to resolve the molecular determinants for rapid degradation of free TCR subunits (Bonifacino et al, 1989;Bonifacino et al, 1990;Fang et al, 2001;Fayadat and Kopito, 2003;Huppa and Ploegh, 1997;Lenk et al, 2002;Tiwari and Weissman, 2001;Travers et al, 2000;Wileman et al, 1990;Wileman et al, 1993;Yang et al, 1998;Yu et al, 1997;Yu and Kopito, 1999). αTCR is a type I transmembrane protein with a short cytoplasmic tail of 5 amino acids, which is dislocated from the ER, deglycosylated and degraded in the cytosol by proteasomes (Huppa and Ploegh, 1997;Yang et al, 1998;Yu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…αTCR is a type I transmembrane protein with a short cytoplasmic tail of 5 amino acids, which is dislocated from the ER, deglycosylated and degraded in the cytosol by proteasomes (Huppa and Ploegh, 1997;Yang et al, 1998;Yu et al, 1997). Ubiquitination of αTCR is required not only for its targeting to the 26S proteasomes, but also for its retrotranslocation from the ER (Thrower et al, 2000;Tiwari and Weissman, 2001). …”
Section: Introductionmentioning
confidence: 99%